Kesejahteraan Psikologis Pada Orang Tua Anak Penyandang Disabilitas Di Sanggar Inklusi Wijaya Kusuma Kabupaten Sukoharjo - Rantri Mustika Dewi; Sri Ernawati (Pusat Riset dan Inovasi Nasional, 2024)
Psychological well-being is a condition where individuals can accept their strengths and weaknesses as they are, have positive relationships with other people, are able to direct their own behavior, are able to develop their own potential in a sustainable manner, are able to control the environment and have a goal in their life. Parents of children with special needs experience many difficulties in everyday life due to certain limitations that the child has, requiring parents to seek education and ensure that the child gets the same opportunities as normal children, the child must also undergo special therapy to ensure that he develops normally. positive into adulthood. Therefore, the psychological well-being of parents needs to be achieved optimally because parents act as educators and primary caretakers of children which can increase positive development in children. The aim of this research was to determine the psychological well-being of parents of children with disabilities at the Wijaya Kusuma Inclusion Studio, Sukoharjo Regency. The results show that parents have demonstrated several characteristics of psychological well-being, namely in the aspects of self-acceptance, autonomy, mastery of the environment and positive relationships with other people.